Influence of diabetes mellitus on the mineralization ability of two endodontic materials - João Eduardo GOMES FILHO; Índia Olinta de Azevedo QUEIROZ; Simone WATANABE; Luciano Tavares Angelo CINTRA; Edilson ERVOLINO (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of this study was to evaluate the influence of diabetes mellituson tissue response and mineralization ability of Sealapex®and MTA Fillapex® sealers. Twenty-four Wistar rats were divided into two groups: diabetic and non-diabetic. The materials were placed in polyethylene tubes and implanted into dorsal connective tissue of rats for 7 and 30 days. Six animals from each group received injection of calcein, alizarin, and oxytetracycline on days 7, 14, and 21, respectively. The animals were killed after 7 and 30 days and specimens were prepared for histologic analysis by staining with hematoxylin and eosin or Von Kossa or left unstained for polarized light or fluorescence microscopy. On day 7, inflammatory reactions were characterized. Moderate inflammatory responses were observed for all groups and on day 30, a mild inflammatory response against MTA Fillapex® and a moderate inflammatory response against Sealapex® were observed. Von Kossa-positive structures were observed in response to both materials and birefringent structures were observed upon polarized light analysis; these had no relation to the diabetic condition (p > 0.05). The fluorescence intensity was unaffected in diabetic rats (p > 0.05). In conclusion, diabetes mellitus did not influence the tissue response or mineralization stimulated by Sealapex® or MTA Fillapex®.